1986
DOI: 10.1159/000226349
|View full text |Cite
|
Sign up to set email alerts
|

Berberine Sulfate Inhibits Tumor-Promoting Activity of Teleocidin in Two-Stage Carcinogenesis on Mouse Skin

Abstract: Berberine sulfate, an isoquinoline alkaloid isolated from Hydrastis canadensis L., inhibited the effects of the tumor promoters 12–O-tetradecanoylphorbol-13-acetate and teleocidin, such as increased 32Pi-incorporation into phospholipids of cell membrane and hexose transport. Berberine sulfate also markedly suppressed the promoting effect of teleocidin on skin tumor formation in mice initiated with 7,12-dimethyl-benz[a]anthracene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(29 citation statements)
references
References 3 publications
(3 reference statements)
0
29
0
Order By: Relevance
“…Berberine not only induced pgp-170 expression on six cancer cell lines (Figure 1) but also elevated the function of pgp-170 in these cancer cell lines (Figure 2). Nishino et al had found that berberine inhibited the effect of 12-O-tetradecanoylphorbol-13-acetate (TPA)-induced responses (Nishino et al, 1986). In another study, the accumulation of TPA and TPA-induced protein kinase C activity in MDR-expressed KB cells are slightly less than the MDR-negative KB cells (Cloud-Heflin et al, 1996).…”
Section: Discussionmentioning
confidence: 98%
“…Berberine not only induced pgp-170 expression on six cancer cell lines (Figure 1) but also elevated the function of pgp-170 in these cancer cell lines (Figure 2). Nishino et al had found that berberine inhibited the effect of 12-O-tetradecanoylphorbol-13-acetate (TPA)-induced responses (Nishino et al, 1986). In another study, the accumulation of TPA and TPA-induced protein kinase C activity in MDR-expressed KB cells are slightly less than the MDR-negative KB cells (Cloud-Heflin et al, 1996).…”
Section: Discussionmentioning
confidence: 98%
“…The potential effectiveness of berberine is indicated by its use in the Indian Ayurvedic (10), Unani, and Chinese systems of medicine since time immemorial. Berberine has been shown to possess antiinflammatory activities in vivo (11) and preliminary studies have been conducted to determine its anticarcinogenic activity in skin (12). It has been shown to inhibit activator protein 1, a key transcription factor in inflammation and carcinogenesis, in human cell lines (13) and has been shown to possess antitumor properties and effectively inhibit cyclooxygenase-2 transcriptional activity in human colon cancer cells (14,15).…”
Section: Introductionmentioning
confidence: 99%
“…It also exhibits antitumor, antimicrobial, and even antidiabetic effects (31)(32)(33)(34)(35)(36). Moreover, a recent report suggested that BBR may be efficacious in experimental type I diabetes (37), raising the possibility of its use as a treatment for autoimmune diseases.…”
mentioning
confidence: 99%